2022
DOI: 10.1111/aos.15124
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐drug antibodies to brolucizumab and ranibizumab in serum and vitreous of patients with ocular disease

Abstract: Purpose Postapproval reports of intraocular inflammation (IOI) and occlusive retinal vasculitis following intravitreal brolucizumab are accumulating. A role of anti‐drug antibodies (ADAs) to brolucizumab is under current scientific discussion. The purpose of the present study was to measure brolucizumab ADAs in a cross‐sectional ophthalmic patient population and to compare the occurrence of brolucizumab ADAs with that of ranibizumab ADAs. Methods One hundred and ninety‐two serum samples and 54 vitreous samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…[15][16][17][18] In the case of brolucizumab, much higher rates of anti-drug antibodies (ADAs) at baseline as well as induced or boosted during clinical trials have been reported compared with ranibizumab and aflibercept. [19][20][21][22] It is possible that the higher rates of preexisting and treatment-emergent anti-brolucizumab antibodies may help explain the higher rates of inflammation with brolucizumab than with the other anti-VEGF drugs; however, it is unclear what their role is in cases of intraocular inflammation. Of note, with pegcetacoplan, the incidence of ADAs was relatively low in clinical trials; they were detected in 2.5% to 4% of participants in the OAKS and DERBY trials.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] In the case of brolucizumab, much higher rates of anti-drug antibodies (ADAs) at baseline as well as induced or boosted during clinical trials have been reported compared with ranibizumab and aflibercept. [19][20][21][22] It is possible that the higher rates of preexisting and treatment-emergent anti-brolucizumab antibodies may help explain the higher rates of inflammation with brolucizumab than with the other anti-VEGF drugs; however, it is unclear what their role is in cases of intraocular inflammation. Of note, with pegcetacoplan, the incidence of ADAs was relatively low in clinical trials; they were detected in 2.5% to 4% of participants in the OAKS and DERBY trials.…”
Section: Discussionmentioning
confidence: 99%
“…In the trial reported here, no IOI was associated with retinal vasculitis. Busch and colleagues reported higher ADA-positivity rates in participants treated with brolucizumab than in those treated with RBZ (18.2% vs 2.6%). Nevertheless, high ADA levels did not necessarily result in IOI.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the biopsy has potential to guide follow up care. An analysis panel consisting of the concentration of drug [26], drug target [27], downstream proteins [28], proteins in parallel disease processes [29], anti-drug antibodies [30], or other analytes may provide clinicians with an useful supplement to structural imaging as a biomarker to help select appropriate therapy and adjust dose timing [31]. Within research settings, analysis of a liquid biopsy has potential to increase the probability of clinical trial success [32] and identify targets for new therapeutics [33].…”
Section: Plos Onementioning
confidence: 99%